Microarray Expression Profile of lncRNAs and mRNAs in Rats with Traumatic Brain Injury after A2B5+ Cell Transplantation. Issue 10 (October 2017) - Lyu, Qiang; Zhang, Zi-Bin; Fu, Song-Jun; Xiong, Liu-Lin; Liu, Jing; Wang, Ting-Hua
Traumatic brain injury (TBI) may cause neurological damage, but an effective therapy and the associated mechanisms of action have not yet been elucidated. A TBI model was established using the modified Feeney method. A2B5+ cells, an oligodendroglial progenitor, were acquired from induced pluripotent stem cells (iPSCs) by mouse embryonic fibroblasts and were transplanted into the injured site. The neurological severity score (NSS) was recorded on 3 d, 7 d, 11 d, 15 d, and 19 d. Seven days after transplantation, oligodendrocytes 2 (Olig2) and myelin basic protein (MBP) were detected by immunohistochemistry (IHC) and Western blot (WB), and long noncoding RNAs (lncRNAs) and messenger RNAs (mRNAs) were screened by microarray technology. Moreover, we took an intersection of the differentially expressed lncRNAs or mRNAs and scanned 10 kb upstream and downstream of the common lncRNAs. Meanwhile, Gene Ontology (GO) and pathway analysis on mRNAs was performed in the A2B5+ iPSC group. A2B5+ iPSCs survived and migrated around the injury site and differentiated into oligodendrocytes. Meanwhile, the increase in Olig2 and MBP were higher in A2B5+ cell-engrafted rats than that in TBI rats. However, the NSSs in the A2B5+ iPSC group were lower than that in the TBI group. Between the TBI and sham groups, 270 lncRNAs and 1, 052 mRNAs were differently expressed ( P < 0.05, fold change (FC) > 2), while between the A2B5+ iPSC and TBI groups, 83 lncRNAs and 360 mRNAs were differently expressed ( P < 0.05, FC > 2). Meanwhile, 37 lncRNAs and 195 mRNAs were simultaneously changed in the 2 parts. Using bioinformatic analysis, we found the crucial lncRNA and mRNA were ENSRNOT00000052577 and Kif2c in the TBI brain with cell transplantation. This study demonstrated that A2B5+ iPSC grafts effectively improved neurological function, and the mechanism of action was associated with lncRNA and mRNA expression. Therefore, A2B5+ iPSC transplantation could be considered as a new method for the treatment of TBI, and ENSRNOT00000052577 and Kif2c may be new molecular targets or markers for functional improvement.